2021
DOI: 10.1075/lab.20024.fuc
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative use of grammatical gender in Heritage Spanish

Abstract: This paper presents an eye-tracking study using the Visual World Paradigm that tests whether participants are able to access gender information on definite articles and deploy it to facilitate lexical retrieval of subsequent nouns. A comparison of heritage speakers of Spanish with control monolingual speakers of Spanish suggests that the heritage speakers’ performance on this task is qualitatively similar to that of the baseline. This suggests that, despite non-target-like performance in offline tasks targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 51 publications
6
27
0
Order By: Relevance
“…Previous work on facilitative use of gender agreement in the processing of nouns in other populations has suggested that when the experimental method involves a gender cue located on an article that is frequent or obligatory in the language, 2 such results are consistent with two possible accounts: under a syntactic account, participants are in fact accessing abstract syntactic information on the article during processing of the noun phrase; under a probabilistic account, the results reflect a mechanism that relies on surface probabilities between frequently cooccurring article-noun pairs (van Heugten and Shi, 2009;Lew-Williams and Fernald, 2010;Melançon and Shi, 2015). Existing work on HSs in this domain (Fuchs, 2021) is consistent with either account, and therefore further work is needed to adjudicate between the accounts. Under a syntactic account, we should expect to observe HSs' facilitative use of grammatical gender when the gender cue is located on a non-frequent, non-obligatory element within the nominal phrase.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Previous work on facilitative use of gender agreement in the processing of nouns in other populations has suggested that when the experimental method involves a gender cue located on an article that is frequent or obligatory in the language, 2 such results are consistent with two possible accounts: under a syntactic account, participants are in fact accessing abstract syntactic information on the article during processing of the noun phrase; under a probabilistic account, the results reflect a mechanism that relies on surface probabilities between frequently cooccurring article-noun pairs (van Heugten and Shi, 2009;Lew-Williams and Fernald, 2010;Melançon and Shi, 2015). Existing work on HSs in this domain (Fuchs, 2021) is consistent with either account, and therefore further work is needed to adjudicate between the accounts. Under a syntactic account, we should expect to observe HSs' facilitative use of grammatical gender when the gender cue is located on a non-frequent, non-obligatory element within the nominal phrase.…”
Section: Introductionmentioning
confidence: 59%
“…Given this, HSs patterning with adult and child controls in their ability to use gender to facilitate lexical retrieval has implications for the understanding of how the nature of the acquisition process may impact processing abilities. Following Grüter et al (2012) and Montrul et al (2014), Fuchs (2021) suggests that early and naturalistic acquisition of grammatical gender in the speech stream may be crucial for developing robust associations 10.3389/fpsyg.2022.960376 between pre-nominal gender cues and subsequent nouns, as discussed further in section "Discussion. "…”
Section: Background Grammatical Gender In Heritage Languagesmentioning
confidence: 98%
See 3 more Smart Citations